2008
DOI: 10.1128/jcm.01886-07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Aspects of Linezolid Resistance Mediated by the cfr Gene Encoding a 23S rRNA Methyltransferase

Abstract: The cfr (chloramphenicol-florfenicol resistance) gene encodes a 23S rRNA methyltransferase that confers resistance to linezolid. Detection of linezolid resistance was evaluated in the first cfr-carrying human hospital isolate of linezolid and methicillin-resistant Staphylococcus aureus (designated MRSA CM-05) by dilution and diffusion methods (including Etest). The presence of cfr was investigated in isolates of staphylococci colonizing the patient's household contacts and clinical isolates recovered from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 30 publications
1
64
0
5
Order By: Relevance
“…However, the Vitek-2 software recommended that the linezolid susceptibilities should be manually changed to 4 g/ml and that the isolate should be reported as susceptible to linezolid. While the authors of a 2008 study (1) did not encounter problems using the Vitek system, they did report problems with detecting cfr-mediated linezolid resistance using disk diffusion and Etest. The authors found that a cfr-positive MRSA isolate was reported as linezolid susceptible after 24 h of incubation with the Etest and suggested that a longer incubation period was required to detect this resistance phenotype (1).…”
Section: Vol 54 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Vitek-2 software recommended that the linezolid susceptibilities should be manually changed to 4 g/ml and that the isolate should be reported as susceptible to linezolid. While the authors of a 2008 study (1) did not encounter problems using the Vitek system, they did report problems with detecting cfr-mediated linezolid resistance using disk diffusion and Etest. The authors found that a cfr-positive MRSA isolate was reported as linezolid susceptible after 24 h of incubation with the Etest and suggested that a longer incubation period was required to detect this resistance phenotype (1).…”
Section: Vol 54 2010mentioning
confidence: 99%
“…A cfr-positive MRSA isolate from a Colombian patient belonged to ST5/ST221-MRSA-I, and cfr was chromosomally located (1,45). A cfr-positive methicillin-susceptible S. (26).…”
Section: Vol 54 2010mentioning
confidence: 99%
“…In Staphylococcus spp., oxazolidinone resistance is conferred by the Cfr rRNA methylase, encoded by the cfr gene (14,221,223,382). This enzyme methylates the 23S rRNA at position 2503 (382), and the gene is associated with mobile elements (41,243,382).…”
Section: Inhibition Of Protein Synthesismentioning
confidence: 99%
“…Mutation of linezolid binding sites is the most common mechanisms of resistance; however, acquired resistance mechanisms have now been described (7). One example of nonmutational resistance is acquisition of the natural cfr (chloramphenicol-florfenicol resistance) gene, which is a plasmid-carried gene encoding a protein which catalyzes the posttranscriptional methylation of the C-8 atom of a key residue (A2503) in the 23S rRNA (8).…”
mentioning
confidence: 99%